Origins of Instability in Early Republican Mexico - Stevens, Donald Fithian, 1953- (Book collections on Project MUSE., 1991)
In the decades following independence, Mexico was transformed from a strong, stable colony into a republic suffering from economic decline and political strife. Marked by political instability--characterized by Antonio López de Santa Anna's rise to the presidency on eleven distinct occasions--this period of Mexico's history is often neglected and frequently misunderstood.Donald F. Stevens' revisionist account challenges traditional historiography to examine the nature and origins of Mexico's political instability. Turning to quantitative methods as a way of providing a framework for examining existing hypotheses concerning Mexico's instability, the author dissects the relationship between instability and economic cycles; contradicts the notion that Mexico's social elite could have increased political stability by becoming more active; and argues that the principal political fissures were not liberal vs. conservative but were among radical, moderate, and conservative.Ultimately, Stevens maintains, the origins of that country's instability are to be found in the contradictions between liberalism and Mexico's traditional class structure, and the problems of creating an independent republic from colonial, monarchical, and authoritarian traditions.